MANAJEMEN KONFLIK DALAM LINGKUNGAN SEKOLAH(Strategi Preverentif Dan Resolusi Berbasis Kepemimpinan Kolaboratif) - Reyhana Azzahra; Muhammad Hasan Basari; Aura Rifasya; Ummu Hani Hauliyah Hakim (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Conflict management is essential in fostering a positive learning environment in schools. This study focuses on conflict resolution and preventative measures utilizing collaborative leadership. Data were gathered via observation, interviews, and a review of the literature using a qualitative descriptive methodology. The findings suggest that collaborative leadership can improve conflict management by fostering open communication, participatory decision-making, and stronger relationships among members of the school community. Proven methods of prevention include teacher training, joint regulation creation, and school value reinforcement.